The Variability of Pelvic Obliquity Measurements in Patients with Neuromuscular Scoliosis. Issue 1 (January 2021) - Karkenny, Alexa J.; Magee, Lacey C.; Landrum, Matthew R.; Anari, Jason B.; Spiegel, David; Baldwin, Keith
Abstract : Background: Pelvic obliquity (PO), or pelvic alignment in the coronal plane, is an important radiographic parameter to indicate fusion levels and judge success of scoliosis correction in patients with neuromuscular scoliosis. There are multiple commonly used techniques to measure PO that have good to excellent interrater and intrarater reliability, but these different methods yield inconsistent values when used on the same radiograph. This study evaluates the inconsistency in the magnitude of PO measurements for patients with neuromuscular scoliosis among 5 common measurement techniques. Methods: Radiographs of 63 patients with neuromuscular scoliosis were evaluated by 5 raters. Each rater measured PO on each radiograph using the Osebold, O'Brien, Allen and Ferguson, Lindseth, and Maloney techniques. Patients were divided into 2 cohorts based on coronal balance or imbalance. Interrater and intrarater analyses were performed using a 2-way random effects model to calculate absolute agreement. The mean difference in PO between all possible pairs of the techniques was compared using a 2-tailed t test. Results: The Maloney and Osebold techniques demonstrated excellent interrater reliability, and the Maloney, Osebold, and O'Brien techniques demonstrated excellent intrarater reliability. Significant differences in PO measurement were found in 6 of the 10 comparisons for the balanced spines and 8 of the 10 comparisons for the unbalanced spines. Variability in measurement was captured by best-fit lines, which demonstrated greater dispersion between the means for the Osebold and Maloney techniques in the unbalanced spines than in the balanced spines. Conclusions: To our knowledge, this study is the first to evaluate mean differences in magnitude of PO among common measurement techniques while accounting for coronal imbalance. Although there is no gold standard for measuring PO, the Maloney and Osebold techniques are the most consistent. This study suggests that those 2 techniques can be used interchangeably when the spine is coronally balanced, but the Osebold technique becomes more inconsistent than the Maloney technique when coronal imbalance exceeds 2 cm. Clinical Relevance: This information is relevant to surgeons using PO to plan fusion levels and striving for objective ways to judge correction intraoperatively as well as for researchers compiling PO data from multiple centers or studies.